Children's Bodies in Schools: Corporeal Performances of Social Class - Henry, Sue Ellen; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Bringing together sociology of the body with powerful examinations of educational theory and social class, Henry examines how children's experiences of school and pedagogy are shaped by their bodies and the ideas of social class and class identity that their bodies carry.
Keywords: Science; Science; Science, general